Hubungan Kepatuhan Hemodialisis dengan Disfungsi Seksual Wanita Usia Subur di RSUD Ungaran - Yacomina Kuway; Tressia Sujana; Rifatolista Tampubolon (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Abstract Female patients with chronic kidney failure undergoing hemodialysis therapy have various health problems, one of which is sexual dysfunction. Sexual dysfunction was experienced in the form of sexual desire disorders, arousal, lubrication, orgasm, satisfaction, and pain. This study aims to determine the relationship of hemodialysis compliance with sexual dysfunction of women of childbearing age at Ungaran District Hospital. The research design used is the quantitative correlation with a cross-sectional approach. The research sample is women of childbearing age with an age range of 25-34 years to 35-44 years. The results of the study with Chi-Square analysis showed a significance value (Sig) 0.542 (p = 1,000) or > 0.05 which means there was no significant relationship between hemodialysis adherence with sexual dysfunction of women of childbearing age at Ungaran District Hospital. the conclusion of this study is that factors such as lack of sexual desire are the main reason there is no relationship between the two variables. Keywords: Female patients with chronic renal failure, hemodialysis compliance, sexual dysfunction. Abstract Pasien wanita gagal ginjal kronik yang menjalani terapi hemodialisis mempunyai berbagai masalah kesehatan, salah satunya ialah difungsi seksual. Disfungsi seksual yang dialami berupa gangguan keinginan seksual, gairah, pelumasan, orgasme, kepuasan dan nyeri. Penelitian ini bertujuan untuk mengetahui hubungan kepatuhan hemodialisis dengan disfungsi seksual wanita usia subur di RSUD Ungaran. desain penelitian yang digunakan adalah kuantitatif korelasi dengan pendekatan cross-sectional. Sampel penelitian ialah wanita usia subur dengan rentang usia 25-34 tahun hingga 35-44 tahun. Hasil penelitian dengan analisis Chi-Square menunjukan nilai signifikansi (Sig) 0,542 (p=1.000) atau > 0,05 yang berarti tidak terdapat hubungan yang bermakna antara kepatuhan hemodialisis dengan disfungsi seksual wanita usia subur di RSUD Ungaran. kesimpulan dari penelitian ini adalah faktor seperti kurangnya keinginan seksual menjadi alasan utama tidak terdapat hubungan antara kedua variabel. Kata Kunci: Pasien wanita gagal ginjal kronik, kepatuhan hemodialisis, disfungsi seksual.